Through the secret door - Hull , Eleanor; Riswold , Gilbert (Boston : United Church Press, 1963)
The story follows a young boy who discovers a mysterious secret door in his house. When he steps through it, he enters a magical and mysterious world that challenges his courage and curiosity. As he explores, he learns lessons about bravery, imagination, and self-discovery, encountering strange characters and unexpected adventures along the way. The book combines elements of fantasy and coming-of-age, making it both entertaining and thought-provoking for young readers.